TEACHER PROFESSIONALISM AS A KEY FACTOR IN CREATING A POSITIVE LEARNING ENVIRONMENT - Agusthina Siahaya (Adisam Publisher, 2024)
In creating quality education, teachers must have high qualifications, competence and dedication in carrying out their professional duties. Teachers are the key to the success of an educational institution. The purpose of this article was to help readers comprehend the significance of the role that professional instructors play in raising educational standards and fostering a supportive learning environment. The literature study approach from a variety of sources, including books, papers, and journals, was employed in this composition. The writing's outcomes demonstrate how crucial a teacher's professionalism is to students' learning progress. The conclusion of this research is that the main components of competence that a professional teacher must have are professional competence, pedagogical competence, social competence and personality competence. Some of the roles of teachers in creating a positive learning atmosphere are teachers as class managers, facilitators, mediators, motivators and informers.